User experience re-mastered : your guide to getting the right design - Wilson, Chauncey (Morgan Kaufmann series in interactive technologies., 2010)
Good user interface design isn't just about aesthetics or using the latest technology. Designers also need to ensure their product is offering an optimal user experience. This requires user needs analysis, usability testing, persona creation, prototyping, design sketching, and evaluation through-out the design and development process. User Experience Re-Mastered takes tried and tested material from best-selling books in Morgan Kaufmann's Series in Interactive Technologies and presents it in typical project framework. Chauncey Wilson guides the reader through each chapter, introducing each stage, explaining its context, and emphasizing its significance in the user experience lifecycle. This gives readers practical and easily applicable direction for creating web sites and web applications that ensure the ultimate experience. A must read for students, those new to the field, and anyone designing interfaces for people! A guided, hands-on tour through the process of creating the ultimate user experience - from testing, to prototyping, to design, to evaluation Provides tried and tested material from best sellers in Morgan Kaufmann's Series in Interactive Technologies Presents material from luminaries field in a straightforward, easy to digest format ideal for students and those new to the field.